METABOLIC CONSEQUENCES OF THE CO-OCCURRENCE OF OBESITY AND ANEMIA AMONG HOUSEWIVES: A COMPARISON OF THE GENERALIZED AND ABDOMINAL OBESITY (Journal of Medical & Health Sciences Review, 2025)
A hospital-based cross-sectional study was conducted to investigate the metabolic consequences of the co-occurrence of obesity and anemia among housewives in Bhakkar. The study included 200 obese anemic subjects (100 with general obesity and 100 with abdominal obesity) of age 21-60 years. Subjects’ selection was made through convenience sampling technique. The socio-demographic information was obtained by interviewing the subjects and recorded in specific questionnaire. Anthropometric measures included weight, height and waist circumference (WC). Body mass index (BMI) was calculated using the measured weight and height of subjects. Biochemical data included hemoglobin level, fasting blood glucose level and lipid profile. The clinical data included only blood pressure measurement. Hemoglobin level was used as the first screening step in selection of subjects; whereas, BMI and WC were used as second screening step. The collected data was analyzed using the statistical software SPSS and the results were presented in the form of either mean±SD or frequencies (%). Relationship of BMI and WC with the biochemical and clinical variables was determined using Pearson's correlation. The results revealed that the overall mean age of subjects was 39.9±10.1 years. Mean hemoglobin level of all subjects was 10.6±1.3mg/dl. Most of the subjects (54%) were mildly anemic. Mean weight, height, BMI and WC of all subjects were 80.7±9.8 kg, 165.0±4.9 cm, 29.7±3.6 kg/m2 and 90.1±10.1 cm, respectively. Overall, Most of the obese anemic subjects (54%) had elevated glucose levels with an overall mean fasting blood glucose level (FBG) level of 109.4±18.9 mg/dl. The abdominally obese subjects had significantly higher mean FBG level than the generally obese subjects (p